Evaluation and Proportion in Nasal Filling with Hyaluronic Acid - Bravo, Bruna Souza Felix (J Clin Aesthet Dermatol, 2018)
The nose is an essential feature when considering the aesthetic appeal of the face. As aesthetic preferences vary from person to person, the concept of the “ideal” nose must be applied on a case-by-case basis, with respect to the classical patterns of anthropometry, sex, ethnic group, and psychosocial factors. Interest in less invasive procedures for nasal correction has increased considerably, among which is the emerging use of hyaluronic acid for nonsurgical rhinoplasty. In this article, the authors present an objective review of the anatomy of the nasal region, the evaluation and indications of nasal filling with hyaluronic acid, a description of the technique, and brief discussion of associated complications.